Sorption studies of nylon - Tng, Shu Zheng. (2009)
Sorption is the penetration and dispersion of the molecules of an ambient gas, vapour or liquid onto and/or throughout a solid such as polymer. Sorption studies of polymers were performed to analyze the polymer’s behaviour due to the presence of penetrant. In this experiment, sorption behaviours (weight gained and concentration) of nylon-6,6 and nylon-6 in ethanol–water mixtures of different composition were studied.